Influences of Mass Media, Family, and Friends Towards Adolescents’ Smoking in Yogyakarta - Liem, Andrian (UI Scholars Hub, 2014)
The number of youth who try smoking is increasing, and the onset is getting earlier. This study tries to answer “Who or what are the main reasons of smoking for Indonesian adolescents, especially in DI Yogyakarta?” through Theory of Triadic Influences (cultural environment, social situation, and biology/personality). Current studies have focused only on cultural environment (mass media) and social situation (family and friends) influence. The sampling was conducted through convenience sampling method to 390 adolescents from 12 junior high schools in DI Yogyakarta. The average age of the subjects is 14 years old, with male to female ratio 55.6%:44.4%. The data were collected through anonymous questionnaires consisting of seven parts. Descriptive analysis was applied to the collected data by means of Chi Square test and logistic regression. The result showed that friends’ influence was the strongest compared with mass media and family to adolescents’ smoking behavior. Among several sub-agents of mass media, it was not television but billboards that had stronger influence. Parents’ influence was not significant compared with siblings and other family members. School friends’ influence was not significant compared with friends from school and other friends. Based on the findings, the applicable proposed interventions are denormalization of cigarette consumption and systematic intervention, such as raising the tobacco price, limiting advertisement and promotion, also regulating tobacco sales.